Analisis Komparasi Daya Saing Ekspor Komoditi Kayu Manis di Provinsi Jambi dan Sumatera Barat - Chatra, Afdhal (Jurnal MeA (Media Agribisnis), 2024)
This research aims to analyze the export competitiveness of cinnamon commodities in Jambi Province and West Sumatra Province in the domestic and international markets. The analysis tool for this research uses the Revealed Comparative Advantage (RCA) index during 2011-2023. The research results show that the RCA value of cinnamon in the domestic market of West Sumatra Province is higher compared to Jambi Province. Meanwhile, the RCA value of cinnamon in the international market, Jambi Province and West Sumatra Province have not shown a strong comparative advantage, with an average RCA value < 1 From the results of this research, several policies are recommended to increase the competitiveness of cinnamon exports, including providing subsidies and incentives to farmers and exporters, developing transportation and logistics infrastructure, supporting research and development (R&D), promoting international trade, providing training and upgrading. capacity, as well as implementation of international quality standards and certification. The implementation of these policies is expected to increase the production and quality of cinnamon that meets international standards, as well as strengthen the competitiveness of Indonesian cinnamon products in the global market.